PERLINDUNGAN DATA PRIBADI DALAM ERA DIGITAL :REGULASI DAN PRAKTIK HUKUM DI INDONESIA: Protection of Personal Data in the Digital Era: Regulations and Legal Practices in Indonesia - Liuhua, Wei (Fakultas Hukum, Universitas Trisakti, 2025)
This research aims to review and understand the practice of personal data protection in Indonesia. The case of personal data leakage in Indonesia some time ago caused various impacts, one of which was financial loss and various misuse of personal data by irresponsible people. The Indonesian government in response to the case immediately passed the Personal Data Protection Law or UU PDP as a legal effort to ensure the protection of personal data of the Indonesian people. This research uses a conceptual approach to review the legal practice of the PDP Law in Indonesia. Based on the results of the study, the legal practice of the PDP Law still found various challenges such as overlapping regulations, besides that even though there is a PDP Law, cases of data leakage are still found in Indonesia.